Optimizing the bioenergy water footprint by selecting SRC willow canopy phenotypes: regional scenario simulations. (13th February 2019) - Richard, Benjamin; Richter, Goetz M; Cerasuolo, Marianna; Shield, Ian
Abstract: Background and Aims: Bioenergy is central for the future energy mix to mitigate climate change impacts; however, its intricate link with the water cycle calls for an evaluation of the carbon–water nexus in biomass production. The great challenge is to optimize trade-offs between carbon harvest and water use by choosing cultivars that combine low water use with high productivity. Methods: Regional scenarios were simulated over a range of willow genotype × environment interactions for the major UK soil × climate variations with the process-based model LUCASS. Soil available water capacity (SAWC) ranged from 51 to 251 mm and weather represented the north-west (wet, cool), north-east (dry, cool), south-west (wet, warm) and south-east (dry, warm) of the UK. Scenario simulations were evaluated for small/open narrow-leaf (NL) versus large/closed broad-leaf (BL) willow canopy phenotypes using baseline (1965–89) and warmer recent (1990–2014) weather data. Key Results: The low productivity under baseline climate in the north could be compensated by choosing BL cultivars (e.g. 'Endurance'). Recent warmer climate increased average productivity by 0.5–2.5 t ha −1, especially in the north. The modern NL cultivar 'Resolution' had the smallest and most efficient water use. On marginal soils (SAWC <100 mm), yields remained below an economic threshold of 9 t ha −1 more frequently under baseline than recent climate. In the drought-prone south-east, 'Endurance' yielded less than 'Resolution', which consumed on average 17 mm year −1 less water. Assuming a planting area of 10 000 ha, in droughty years between 1.3 and 4.5 × 10 6 m 3 of water could be saved, with a small yield penalty, for 'Resolution'. Conclusions: With an increase in air temperature and occasional water scarcities expected with climate change, high-yielding NL cultivars should be the preferred choice for sustainable use of marginal lands and reduced competition with agricultural food crops.